The role of rural women entrepreneurship in the development of food tourism (case study: servlet village located in guilan province) - Hosseinpour Niazi, Samaneh; Salehi, Homa; Taj, Shohreh (Applied Family Therapy Journal (AFTJ), 2022)
Aim: In recent years, the tourism industry has focused on major shopping malls, resorts, hotels and places to visit, but in recent years, food tourism has become one of the main pillars of the industry. In the meantime, creative, innovative and innovative women as entrepreneurs have been the source of great changes in the fields of industry, production and services in rural areas. Therefore, the purpose of this study is to investigate the role of rural women entrepreneurship in the development of food tourism (case study, Serulat village located in Guilan province). Method: The present research is descriptive-analytical in nature and method and is applied in terms of purpose and strategic development. The statistical population of the study consists of 30 women entrepreneurs in Serulat village of Guilan province. This village has a population of 509 people. 261 men and 248 women live in this village. The required sample size was calculated using Cochran’s formula at 95% confidence level and 1% error for this village of 93 people. In this research, the library method has been used to collect information related to the subject for the theoretical foundations of the research and also the field method has been used to conduct a questionnaire and conduct interviews with village officials and experts. Data analysis was performed by trait independence test using chi-square distribution. Resutls: The results showed that there is a significant relationship between the individual characteristics of rural women entrepreneurs and the development of food tourism. Conclusion: Considering that it is difficult for women entrepreneurs to create and maintain a business; Therefore, politicians should help by creating a favorable environment to promote women’s entrepreneurship.